The John Eggleston Memorial Lecture: DATA 2005 Design and Technology for the Conceptual Age - Hutchinson, Patricia (Design and Technology Education: An International Journal, 2008)
Twenty years ago I spent a year studying the Design Process in CDT in the UK on a Fulbright Scholarship. Pre-National Curriculum, it was an exciting time to be a technology educator. Among the people whose work had impressed me in my doctoral research were Bruce Archer, Ken Baynes and John Eggleston. It is on Professor Eggleston’s influence on American technology education that I attempted to focus for this lecture. John Eggleston was responsible for many of the values that underpin our conception of Design and Technology in both the US and the UK. His ideas are among the most humanizing principles underlying our conception of design and technology as a new school subject for all students. Recently in the US, however, technology education has begun to take engineering as its professional model, a considerably narrower view of our enterprise than some of us have envisioned. There are many reasons for this, political, cultural and economic. The most significant may be a result of an expected shortfall of engineers, since tightened national security has limited the number of foreign engineering students who have traditionally studied and then stayed to work in the US. This influence tends to shift technology education from general education to a pre-professional or pre-vocational offering. During the 1990s, many of us in technology education based our view of the field on a continuum of designerly activity ranging from the artistic to the scientific. A recent book by Daniel Pink, titled A Whole New Mind, supportsthe view that the skills most valuable for the highly technological future, in both careers and life in general, may not be those left-brained skills associated with engineering, but rather the more right-brained capabilities typical of the designer. The left-brain/right-brain juxtaposition is a key component of Pink’s argument. He points out that information technology is replacing or at least devaluing the logical, analytical capabilities of the left brain, much as mechanical devices devalued human strength and dexterity and took us into the industrialage. Pink feels we are now moving beyond the information age and into the conceptual age, where creativity and empathy will be the critical factors in success of all kinds. He identifies six “senses” that will be of major importance in business, healthcare, law, economics and other key enterprises and provides strategies for assessing and strengthening these senses. Many of the activities he suggests would be familiar to design and technology teachers. The whole new mind that Pink describes is highly consistent with the broad definition of technology education articulated by John Eggleston. Pink’s observations suggest that the left brain-directed abilities that currently characterize engineering are only part of the picture of the technological literacy and capability; hopefully, a more holistic version of technology education will lead the way into the Conceptual Age.